The Role of SIM in Increasing PPDB - Oktaviani Permatasari; Ayuba Kambai Ibrahim (LPPM Institut Teknologi dan Sains Mandala, 2025)
Management Information Systems (MIS) in general have an important role in the world of education. Meanwhile, PPDB is often carried out online in many regions to simplify the process and increase transparency. The education Management Information System (SIM) can help parents of students in finding information related to New Student Admissions (PPDB). SIM can also provide other benefits for parents, such as making it easier to monitor children's absences, making it easier to monitor children's grades, and getting information provided by the school. The aim of this research is to review previous research that examined school SIMs, as well as developing school SIMs to increase PPDB. The method used is Systematic Literature Review (SLR), which is a systematic research method for collecting, critically evaluating, integrating, and presenting findings from various research studies about research questions or topics of interest.